Health State and Barriers to the Provision of Health Services among Forcibly Displaced Myanmar Nationals in Bangladesh - Nurunnabi, Mohammad; Haque, Md Amdadul; Khanam, Sadia; Tabassum, Tahsin Tasneem; Akhter, Farzana; Islam, ANM Shamsul (Eastern Medical College Journal, 2024)
Background: Forcibly displaced Myanmar nationals (FDMNs) are one of the most persecuted minorities groups, suffering from an abundance of health issues. They are exposed to a wide range of stressful events that are associated with adverse health consequences, which leads to decreased life expectancy due to increased morbidity and mortality. Methodology: A descriptive cross-sectional survey among conveniently selected 203 healthcare workers (HCWs) to assess the health state and barriers to the provision of health services to FDMNs in the Kutupalong and Balukhali camps at Ukhiya Upazilla, Cox's Bazar. Data were collected by face-to-face interviews by using a semi-structured questionnaire. Results: The mean age of the HCW was 29.2±3.6 years and mean service duration was 5.8±4.1 months. Most of the health facilities provided treatment for CDs (62.5%) and NCDs (80.0%). About one-third of the facilities had no laboratory facilities for diagnosing CDs (32.2%) and NCDs (40.0%). More than half of HCCs (55.0%) were maintain sterilization processes, such as boiling (90.9%), chemical components (45.5%) and an autoclave machine (13.6%). One-fourth of the HCWs (25.6%) get training during their joining times and above two-thirds of the HCWs (69.5%) received training after joining their service. The most frequently cited challenges faced during the provision of health services were transportation barriers (96.4%), language barriers (87.2%), scarcity of drugs (67.5%), vague disease histories (60.9%), unfavorable weather (59.4%) and electricity problems (44.7%). Conclusion: This study suggests that an organized primary healthcare service, specially designed for communicable and non-communicable disease prevention and management is necessary to improve health condition of FDMNs. Eastern Med Coll J. July 2023; 8 (2): 33-39